2017
DOI: 10.1111/jre.12482
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides as a possible interlink between periodontal diseases and its risk factors: A systematic review

Abstract: Antimicrobial peptides (AMPs) play a critical role in controlling innate and acquired immune responses. Local dysregulation of AMP is implicated in the pathogenesis of periodontal diseases as a response to periodontal pathogen challenge. Changes in AMP expression also characterize tobacco smoking, diabetes mellitus, obesity and rheumatoid arthritis, which are established risk factors of periodontal diseases, suggesting AMP may act as putative mechanistic links between these. The aim was to evaluate and summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 91 publications
(198 reference statements)
2
19
0
3
Order By: Relevance
“…14 More recently, it has been recognized as playing a critical role in immune regulation due to its pro-and anti-inflammatory properties. 11 A growing number of studies are supporting its role in driving chronic inflammation including inflammatory bowel disease, 15 lung cancer, 16 chronic obstructive pulmonary disease, 17 systemic sclerosis, 18 systemic lupus erythematosus (SLE), and RA, 19 rosacea, psoriasis, and atopic dermatitis. 20 All these conditions have been associated with overexpression of LL-37 which is responsible for enhancing the local tissue inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 More recently, it has been recognized as playing a critical role in immune regulation due to its pro-and anti-inflammatory properties. 11 A growing number of studies are supporting its role in driving chronic inflammation including inflammatory bowel disease, 15 lung cancer, 16 chronic obstructive pulmonary disease, 17 systemic sclerosis, 18 systemic lupus erythematosus (SLE), and RA, 19 rosacea, psoriasis, and atopic dermatitis. 20 All these conditions have been associated with overexpression of LL-37 which is responsible for enhancing the local tissue inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…22 A systematic review has suggested that LL-37 may be a possible link between CP and RA. 19 Therefore, this study aimed to evaluate the levels of salivary and serum LL-37 of CP subjects with and without RA and its correlation with disease parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Na AR, a elevação de IL-6 está correlacionada com a destruição articular e progressão da doença (BRZUSTEWICZ; BRYL, 2015). Desse modo, AR e PE estão associadas a altos e persistentes níveis de IL-6 (BARTOLD;HAYNES, 2005;SCHETT, 2007;BRENNAN;McINNES, 2008;de PABLO et al, 2009;GARLET, 2010;LI;COCHRAN, 2011 (YU et al, 2007;ESKAN et al, 2012). Outro achado interessante é que, quando a terapia de bloqueio de TNF-α foi administrada, em modelo de CIA e em humanos, levando a uma diminuição de TNF-α, ocorreu também um aumento na expressão de células Th17 e Th1, produtoras de IL-17 e IFN γ, respectivamente (NOTLEY et al, 2008).…”
Section: Discussionunclassified
“…Tanto as doenças periodontais como vários de seus fatores de risco estabelecidos envolvem perturbações no eixo imune-inflamatório (LI et al, 2018). Há extensas evidências epidemiológicas e experimentais fundamentando o papel de vários fatores de risco na iniciação, progressão e severidade da DP (GENCO; BORGNAKKE, 2013).…”
Section: Doença Periodontal: Etiopatogenia E Relação Com Doenças Sistunclassified
See 1 more Smart Citation